The Concept of Freedom in The Holy Quran (A Thematic Study) - Jilani Ben Touhami Meftah (UIN Sunan Gunung Djati Bandung, 2017)
This paper deliberates with the concept of freedom in the Holy Quran by analyzing the concept and highlighting its theoretical and applied features. This paper is divided into an introduction and three sections: The first part deals with the principle of freedom and its status in the Qur’an, it was found that freedom is a human nature and its codification and being under human responsibility had begun since man was selected as a vicegerent (Khalifah) in the earth. The second part deals with the freedom in its practical aspect by explaining some Quranic stories, which is considered good practical examples for freedom especially in its intellectual facet. It also explains the influence of Quranic meaning of freedom on the attitude of people and the role that it can play in the civilizational progress. The third part summaries of the paper: Freedom as comprehensive concept is a Quranic objective. Freedom is a prerequisite for man to carry his duty as the boss of Universe (Khalifah). Freedom is a requirement for any social contract and for any civilizational progression. The methodology used in this paper is the methodology of analysis and synthesis.